Living with Life a Theater of Witness piece with eight men serving life sentences. (TOVA, 2003)
"Living with Life is a unique and emotionally powerful video based on an original, live theater piece featuring eight men serving life sentences at the State Correctional Institution in Chester, PA. This video illuminates their true stories about their lives before incarceration and during their more than 177 cumulative years behind bars. The video documents the performance in spoken word and song, enhanced by interviews with the men and with their families. The video speaks to issues of remorse, forgiveness, patience, strength and spirit."
Keywords: $aPrisons $zUnited States; $aCorrections $zUnited States